FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DI SEKTOR PERTANIAN PADA BURSA EFEK INDONESIA TAHUN 2015-2019 - Sukarta Atmaja (Jurnal Manajemen dan Bisnis, 2020)
For companies that has been go public, the wealth of the owner is reflected from their value in the stock market. The higher the value of the stock market is, the greater the wealth of the owner is. Company value in the agricultural sector experienced a trend of decline during the years 2015-2019. Factors that affect company value are capital structure, corporate risk, and profitability of the company. This research uses a sample of 8 companies obtained through the method of judgemental sampling. The Data analysis technique used multiple regression analysis model 1 and multiple regression analysis model 2, which has been tested by classic assumption supported by the company’s value measurement according to several tools of measurement. The results showed that the structure of capital, profitability, and corporate risk simultaneously affect the company’s value significantly. Partially, corporate risk and capital structure have a negative effect and are not significant to the company's value. While profitability has a positive effect and significantly affects the company’s value. With the placement of measured control variable for the company, the influence of capital structure and profitability increase the value of the company, although not significantly. The management doesn’t need to add debt because will has no effect on the company’s value. Profitability should be noticed because it can be a positive signal for investors who have an impact on the company’s value.